Treatment of periodontal disease with an Er,Cr:YSGG laser in rats exposed to cigarette smoke inhalation - Pavone, Chaine [UNESP]; Nogueira, Andressa Vilas Boas [UNESP]; Oliveira, Guilherme José Pimentel Lopes de[UNESP]; Scardueli, Cássio Rocha [UNESP]; Cerri, Paulo Sérgio [UNESP]; Marcantonio Júnior, Elcio [UNESP]; Marcantonio, Rosemary Adriana Chiérici [UNESP] (Springer Nature, 2015)
The purpose of this study was to evaluate the erbium, chromium:yttrium-scandiumgallium-garnet (Er,Cr:YSGG) laser irradiation in the treatment of periodontitis in rats exposed to cigarette smoke inhalation (CSI). Ligatures were placed in the maxillary second molars. After a 15-day period, the ligatures were removed and 180 animals were randomly divided into six groups: (1) CSRP group—CSI and manual scaling and root planing (SRP) treatment; (2) CL group—CSI and Er,Cr:YSGG laser irradiation; (3) CSRP + L group—CSI, SRP, and Er,Cr:YSGG irradiation; (4) SRP group—manual SRP; (5) L group—Er,Cr:YSGG irradiation; (6) SRP + L group—SRP and Er,Cr:YSGG irradiation. At 7, 15, and 30 days after treatments, animals were euthanized and histologic, histometric, immunohistochemistry, and real-time PCR analyses were performed. Histometrically, no differences were observed in the SRP, L, and SRP + L groups exposed to CSI. The CSRP group showed more bone formation at 30 days than at 15 days (p < 0.01) but less bone at 30 days than the CL group at 30 days (p < 0.05). Immunohistochemical staining was positive for osteoblasts, fibroblasts, and osteoclasts. Real-time PCR showed more (vascular endothelial growth factor) VEGF expression in the L (p < 0.05) and SRP + L (p < 0.01) groups at 30 days than at 15 days and less VEGF expression in the CSRP group at 30 days than at 15 days (p < 0.05). There was no difference in fibroblast growth factor (FGF) expression. The Er,Cr:YSGG laser irradiation promotes favorable conditions for tissue repair even in animals exposed to CSI, with similar results as those achieved from manual scaling and root planing.
Keywords: Er,Cr:YSGG; Periodontal disease; Smoke; Laser